2016
DOI: 10.1142/s0217984916501335
|View full text |Cite
|
Sign up to set email alerts
|

Site preferences and effects of X (X = Mn, Fe, Co, Cu) on the properties of NiAl: A first-principles study

Abstract: The site preference of X (X = Mn, Fe, Co, Cu) in NiAl and its effects on structural, electronic and elastic properties were investigated by performing first-principles calculations using density functional theory (DFT). Formation enthalpy calculations show that adding X increases the formation enthalpy of NiAl, indicating that X addition reduces the stability of system. The site preference was investigated by calculating the transfer energy of NiAl alloys with X. The results further exhibit that Mn, Fe and Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…These findings are consistent with literature data: Duncan et al used atom probe field ion microscopy to show Fe preferentially occupying Al sites in NiAl (Duncan et al, 1994). Other studies found Cr clearly preferring Al sites (Medvedeva et al, 1998), while Co is found on the Ni sites, which is to be expected from the chemical similarity of the two elements (Li et al, 2016). It has to be noted that all these studies were conducted for very low concentrations of the substituting elements (Jones, 2003).…”
Section: Directional Solidificationsupporting
confidence: 90%
“…These findings are consistent with literature data: Duncan et al used atom probe field ion microscopy to show Fe preferentially occupying Al sites in NiAl (Duncan et al, 1994). Other studies found Cr clearly preferring Al sites (Medvedeva et al, 1998), while Co is found on the Ni sites, which is to be expected from the chemical similarity of the two elements (Li et al, 2016). It has to be noted that all these studies were conducted for very low concentrations of the substituting elements (Jones, 2003).…”
Section: Directional Solidificationsupporting
confidence: 90%
“…Doping Ti and Nb has little effect on Co and W atoms, but has a great effect on Al atoms, for the density of states. In figure 2(b), the DOS value of Al atoms in the system with Ti occupying the W 6 site is greater than that in the system with Ti doped in the Al 2 site, indicating that the former system is more stable [40], which is consistent with the previous result that is acquired from the formation enthalpy. In addition, the pseudogap of the former is narrower than that of the latter, which reveals that the bond of the former is more metallic than the latter [38].…”
Section: Electronic Structuressupporting
confidence: 88%
“…The brittle-ductile behaviors of materials can be evaluated based on their calculated polycrystalline elastic properties. The intrinsic ductility and brittleness of materials can be predicted using an important comprehensive criterion that includes the ratio of bulk modulus to shear modulus B/G, Poisson's ratio ν, and the Cauchy pressure C 12 -C 44 [31][32][33]. Usually, a ductile material can be obtained when B/G > 1.75, ν > 0.26, and C 12 -C 44 > 0 are concurrently satisfied.…”
Section: Elastic Propertiesmentioning
confidence: 99%